The Structure and Dynamics of Tax Revenue in Nepal: An Analysis of Trends, Composition, and Fiscal Sustainability - Lamichhane, Bhubaneshwar (Academia Research Journal, 2026)
The investigation reveals that tax revenue forms more than 80% of government income, with VAT alongside income taxes and customs and excise duties serving as primary sources. The 1997 introduction of VAT resulted in it now representing 32. Tax revenue from income tax stands at 4% despite significant growth because exemptions, such as agricultural income, keep it limited. An intricate relationship emerges between tax revenue and GDP as the tax-to-GDP ratio climbs beyond 8. The percentage dropped from 65% in 1981/82 to 21%. The year 2020/21 recorded an 89% value. The persistent fiscal deficit in Nepal emerges from ongoing failures in tax administration combined with unequal policy frameworks. The investigation reveals that expanding the tax base alongside tax system digitisation and adjustments to essential goods VAT rates, combined with improved cross-border coordination, could enhance revenue collection. The study insists on the principle of progressive taxation, and calls for strengthening local government in addition to an enlightened public to attain a balanced development and obedience. Removing these discrepancies will allow Nepal to reduce its dependence on external borrowing while focusing on sustained economic development.